Brain malformations and cognitive performance in spina bifida. (2nd November 2020) - Schneider, Joanna; Mohr, Naomi; Aliatakis, Niko; Seidel, Ulrich; John, Rainer; Promnitz, Gabriel; Spors, Birgit; Kaindl, Angela M
Abstract : Aim: To systematically characterize radiological features of patients with spina bifida, their relationship to cognitive function, and differences between spina bifida aperta (SBA) and spina bifida occulta (SBO). Method: In a retrospective study of 265 patients (117 females, 148 males; median age at imaging 11y, range 1–47y; SBA n =206, SBO n =59), the radiological phenotype was assessed through magnetic resonance imaging (MRI) (SBA n =171, SBO n =59). In 126 patients (SBA n =116, SBO n =10) Kaufman Assessment Battery for Children (KABC) or Wechsler Intelligence Scale for Children, Fourth Edition (WISC‐IV) and Wechsler Adult Intelligence Scale, Fourth Edition (WAIS‐IV) were performed. Results: Patients with spina bifida show numerous brain malformations, always present for SBA but rarely for SBO. The most frequent brain malformations in SBA included abnormal corpus callosum (69%), hypoplastic pons (50%), and hypoplastic mesencephalon (20%). Cognitive total IQ scores were below average in 44% (KABC) to 49% (WISC‐IV) of children with SBA, while almost all children with SBO scored at least average. Stenogyria ( p =0.006), pons ( p =0.003), and mesencephalon hypoplasia ( p =0.01) correlated with lower total IQ score and verbal comprehension. Various brain malformations correlate significantly with several cognitive domains, while lesion level only correlates with processing speed. Interpretation: IQ scores were significantly lower in patients with SBA than in patients with SBO. Verbal competence, perceptual reasoning, and working memory were significantly impaired for SBA and correlated with stenogyria and abnormalities of the midbrain and corpus callosum. What this paper adds: Brain malformations occur more frequently in spina bifida aperta (SBA) than in spina bifida occulta (SBO). Cognitive impairment is less frequent in SBO. Hydrocephalus, stenogyria, midbrain, and corpus callosum abnormalities are associated with lower cognitive function. Difference in prognosis in SBO versus SBA can alter prenatal counselling. What this paper adds: Brain malformations occur more frequently in spina bifida aperta (SBA) than in spina bifida occulta (SBO). Cognitive impairment is less frequent in SBO. Hydrocephalus, stenogyria, midbrain, and corpus callosum abnormalities are associated with lower cognitive function. Difference in prognosis in SBO versus SBA can alter prenatal counselling. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Fletcher and Kulesz on page 244 of this issue. Malformaciones cerebrales y rendimiento cognitivo en espina bífida: Objetivo: Caracterizar sistemáticamente las características radiológicas de los pacientes con espina bífida, su relación con la función cognitiva y las diferencias entre la espina bífida abierta (SBA) y la espina bífida oculta (SBO). Método: En un estudio retrospectivo de 265 pacientes (117 mujeres, 148 varones; mediana de edad en el momento de la obtención de imágenes 11 años, rango 1‐47 años; SBA n = 206, SBO n = 59), el fenotipo radiológico se evaluó mediante resonancia magnética ( IRM) (SBA n = 171, SBO n = 59). En 126 pacientes (SBA n = 116, SBO n = 10) Kaufman Assessment Battery for Children (KABC) o Wechsler Intelligence Scale for Children, Fourth Edition (WISC‐IV) y Wechsler Adult Intelligence Scale, Cuarta edición (WAIS‐IV) fueron realizado. Resultados: Los pacientes con espina bífida mostraron muchas malformaciones cerebrales, siempre presentes en la SBA pero rara vez en la SBO. Las malformaciones cerebrales más frecuentes en la SBA incluyen cuerpo calloso anormal (69%), protuberancia hipoplásica (50%) y mesencéfalo hipoplásico (20%). Los puntajes de CI cognitivo total estaban por debajo del promedio en 44% (KABC), en 49% (WISC‐IV) de los niños con SBA, mientras que casi todos los niños con SBO obtuvieron al menos un puntaje promedio. La estenogiria (p = 0, 006), la hipoplasia de la protuberancia (p = 0, 003) y la hipoplasia del mesencéfalo (p = 0, 01) se correlacionan con una menor puntuación total de CI, incluida la comprensión verbal. Varias malformaciones cerebrales se correlacionan significativamente con varios dominios cognitivos, pero el nivel de la lesión individual se correlaciona con la velocidad del proceso cognitivo. Interpretación: Las puntuaciones de CI fueron significativamente más bajas en pacientes con SBA que en pacientes con SBO. La competencia verbal, el razonamiento perceptivo y la memoria de trabajo serán dañados significativamente por la SBA y se correlacionarán con estenogiria y las anomalías del mesencéfalo y el cuerpo calloso. Malformações cerebrais e desempenho cognitivo em espinha bífida: Objetivo: Caracterizar sistematicamente os aspectos radiológicos de pacientes com espinha bífida, sua relação com a função cognitiva, e diferenças entre espinha bífida aberta (EBA) e espinha bífida oculta (EBO). Método: Em um estudo retrospectivo de 265 pacientes (117 do sexo feminino, 148 do sexo masculino; idade mediana no momento da imagem 11a, variação 1–47a; EBA n =206, EBO n =59), o fenótipo radiológico foi avaliado por meio de exame de ressonância magnétiva (ERM) (EBA n =171, EBO n =59). Em 126 pacientes (EBA n =116, EBO n =10) a Bateria Kaufman de Avaliação para Crianças(BKAC) ou Escala Wechsler de Inteligência para crianças, Quarta edição (WISC‐IV) e Escala Wechsler de Inteligência para Adultos, Quarta edição (WAIS‐IV) foram realizadas. Resultados: Pacientes com espinha bífida mostram numerosas malformações cerebrais, sempre presents em EBA, mas raramente em EBO. As malformações mais frequentes em EBA incluem corpo caloso anormal (69%), ponte hipoplásica (50%), e mesencéfalo hipoplásico (20%). Escores cognitivos totais estavam abaixo da média em 44% (BKAC) a 49% (WISC‐IV) de crianças com EBA, enquanto a maioria das crianças com EBO pontuou pelo menos na média. Estenogiria ( p =0, 006), hipoplasia da ponte ( p =0, 003), e do mesencéfalo ( p =0, 01) correlacionaram com menor escore total de QI e compreensão verbal. Várias malformações cerebrais correlacionam significativamente com vários domínios cognitivos, enquanto o nível da lesão apenas se correlaciona com a velocidade de processamento. Interpretação: Escores de QI foram significativamente menores em pacientes com EBA do que em pacientes com EBO. A competência verbal, raciocínio perceptual, e memória de trabalho foram significativamente afetadas em EBA e correlacionadas com estenogiria e anormalidades no cérebro médio e corpo caloso.